2023
DOI: 10.1167/iovs.64.4.31
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of SRT2104 in Murine Ischemia/Reperfusion Injury Through the Enhancement of Sirt1-Mediated Deacetylation

Abstract: Purpose Strategies for neuroprotection are the main targets of glaucoma research. The neuroprotective properties of SRT2104 administration have been proven in central nervous system degeneration diseases through the activation of nicotinamide adenine dinucleotide-dependent deacetylase-silence information regulator 1 (Sirt1). Here, we investigated whether SRT2104 could protect the retina from ischemia/reperfusion (I/R) injury and the underlying mechanisms. Methods SRT210… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 82 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Moreover, SRT2104 demonstrated a remarkable reduced neuroinflammation after I/R injury. Mechanistic studies further revealed that SRT2104 could effectively reverse the acetylation of p53, NF-κB p65, and Signal Transducer and Activator of Transcription 3 (STAT3) induced by I/R 54 .…”
Section: Srt2104 In Optic Nerve Degenerative Diseasesmentioning
confidence: 99%
“…Moreover, SRT2104 demonstrated a remarkable reduced neuroinflammation after I/R injury. Mechanistic studies further revealed that SRT2104 could effectively reverse the acetylation of p53, NF-κB p65, and Signal Transducer and Activator of Transcription 3 (STAT3) induced by I/R 54 .…”
Section: Srt2104 In Optic Nerve Degenerative Diseasesmentioning
confidence: 99%
“…Despite the enigmatic behavior of resveratrol, it is currently used in many clinical trials and is generally well tolerated. Therefore, it is possible to get past the preclinical stage of investigation for PD, but likely will require bioengineering improvement ( 187 , 188 ).…”
Section: Senolytic and Senomorphic Secondary Metabolites In ...mentioning
confidence: 99%